Combination of sepsis biomarkers may indicate an invasive fungal infection in haematological patients. (19th May 2019) - Stoma, Igor; Karpov, Igor; Uss, Anatoly; Krivenko, Svetlana; Iskrov, Igor; Milanovich, Natalia; Vlasenkova, Svetlana; Lendina, Irina; Belyavskaya, Kristina; Cherniak, Veronika
Abstract: Background: Invasive fungal infections are a major threat to a large cohort of immunocompromised patients, including patients with chemotherapy-associated neutropenia. Early differential diagnosis with bacterial infections is often complicated, which leads to a delay in empirical antifungal therapy and increases risk for adverse outcome. Accessibility and performance of specific fungal antigen and PCR-tests are still limited, while sepsis biomarkers are more broadly used in most settings currently. Methods: Haematological patients hospitalized to receive chemotherapy with proven or probable invasive fungal infection or microbiologically proven bacterial bloodstream infection were included in the study. C-reactive protein was assessed daily during the profound neutropenia period, while procalcitonin or presepsin were measured during the first 48 hours after the onset of febrile episode. Results: There were totally 64 patients included in the study, 53 with bacterial bloodstream infections and 11 with invasive fungal infections. Combination of CRP >120 with PCT <1.25 or presepsin <170 was shown to be a possible combined biomarker for invasive fungal infections in immunocompromised patients, with areas under the ROC-curves: 0.962 (95% CI 0.868 to 0.995) for PCT-based combination and 0.907 (95% CI 0.692 to 0.990) for presepsin-based combination.